2012
DOI: 10.2217/fvl.12.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Treatments on Highly Pathogenic Avian Influenza H5N1, Seasonal and H1N1pdm09 Virus Infections in BALB/c Mice

Abstract: Statins are used to control elevated cholesterol or hypercholesterolemia, but have previously been reported to have antiviral properties. Aims To show efficacy of statins in various influenza virus mouse models. Materials & methods BALB/c mice were treated intraperitoneally or orally with several types of statins (simvastatin, lovastatin, mevastatin, pitavastatin, atorvastatin or rosuvastatin) at various concentrations before or after infection with either influenza A/Duck/ MN/1525/81 H5N1 virus, influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
0
20
0
1
Order By: Relevance
“…Finally, statins have been examined in murine models of influenza A pneumonia. Collectively, it has been shown that several statins have no significant effect on viral clearance, lung injury, weight loss, or mortality [169], although one group found reduced survival in simvastatin-treated mice [170]. …”
Section: A Role For Statins In Host Defense?mentioning
confidence: 99%
“…Finally, statins have been examined in murine models of influenza A pneumonia. Collectively, it has been shown that several statins have no significant effect on viral clearance, lung injury, weight loss, or mortality [169], although one group found reduced survival in simvastatin-treated mice [170]. …”
Section: A Role For Statins In Host Defense?mentioning
confidence: 99%
“…In particular, anti-influenza activity was reported for benzbromarone, ambraxol and tannic acid [168][169][170]. Kinase inhibitors, such as dinaciclib, flavopiridol, SNS-032, and MK2206, and TNF inhibitors, such as etanercept, adalimumab and infliximab, as well as a lipid-lowering simvastatin and antibacterial vancomycin, rifampicin, and erythromycin, were also reported to possess anti-IAV activity [13,104,107,108,116,128,129,147,166,170]. Interestingly, some of the identified inhibitors could be used for treatment of pain and inflammation associated with severe infections [96] (Patent US 20130123345 A1).…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%
“…81 In a much larger study, several different statins were tested against several different influenza viruses in BALB/c mice. 82 No meaningful evidence of protection was shown, but again the infecting dose of virus was highly lethal. Moreover, treatment was given for only a few days, and it is well known that early cessation of statin treatment during an inflammatory illness in both mice and humans leads to a rebound hypercytokinemia and increased mortality.…”
Section: The Host Response To Influenzamentioning
confidence: 99%
“…81,82 For example, studies by several virologists have yet to show that statins are effective in mouse models of influenza, yet many human studies suggest that they are (see above). There is no ready explanation for these discordant results, but it is worth noting that although the molecular mechanisms for the inflammatory responses of humans and mice are in many ways similar, they are quantitatively very different.…”
Section: Animal Studies Of Immunomodulatory Treatment Of Influenzamentioning
confidence: 99%